Association between vitamin D plasma concentrations and VDR gene variants and the risk of premature birth - Letícia Veríssimo Dutra; Fernando Alves Affonso-Kaufman; Fernanda Ramires Cafeo; Milene Saori Kassai; Caio Parente Barbosa; Francisco Winter Santos Figueiredo; Fabíola Isabel Suano-Souza; Bianca Bianco (BMC, 2019)
Abstract Background Premature birth is the main cause of mortality in children under 1 year, and vitamin D deficiency during gestation is associated with prematurity. The effects of vitamin D are mediated by its receptor, which is encoded by the VDR gene. VDR variants-such as single nucleotide variation (SNV)-are associated with increased risk of prematurity, but there are conflicting results. We evaluated serum vitamin D concentrations and the frequency of TaqI/A > G, BsmI/C > T, ApaI/C > A, and FokI/A > T VDR variants in mothers and preterm (PTN) and full-term (FTN) newborns. Methods We conducted a case-control study comprising 40 pairs of mothers and their PTNs (gestational age < 32 weeks and/or weight < 1500 g), and 92 pairs of mothers and FTNs as controls. Genotyping was performed by real-time PCR, and plasma vitamin D concentrations were measured by electrochemiluminescence. Results Vitamin D levels were significantly lower in PTN mothers. Genotypes TaqI/GG and BsmI/TT, and haplotypes AAG (TaqI/A-ApaI/A-FokI/G) and GCA (TaqI/G-ApaI/C-FokI/A) were significantly more frequent in PTN mothers, and genotypes TaqI/AG, ApaI/AA, and FokI/AG resulted in significantly lower vitamin D levels. Genotypes BsmI/TT and ApaI/AA were associated with vitamin D deficiency and 2.36 and 7.99 times greater likelihood of PTB, respectively. Vitamin D levels were also lower in PTNs, although it was not statistically significant. Genotypes BsmI/TT, ApaI/AA, and FokI/GG, and haplotype GAG (TaqI/G-ApaI/A-FokI/G) were significantly more frequent in PTNs. Those with FokI/GG genotypes had significantly lower vitamin D levels. Conclusions VDR variants contribute to variations in vitamin D concentrations and the increased risk of prematurity.